2012
DOI: 10.1094/cchem-07-12-0085-rc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Grain Protein Concentration on Falling Number of Ungerminated Soft White Winter Wheat

Abstract: Falling number (FN) values below 300 sec in the apparent absence of preharvest sprouting are periodically observed in the U.S. Pacific Northwest (USPNW). Wheat in the USPNW is predominantly soft‐grained and often grown under conditions conducive to low grain protein concentration (GPC). Our hypothesis is that low GPC per se could be responsible for some low FN results and not elevated α‐amylase from either sprouting or late‐maturity amylase. The relationship between FN and GPC was investigated using grain from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 8 publications
0
16
2
Order By: Relevance
“…The current study was designed to address this answer while following the best laboratory practices established in the previous study. Ross et al (2012) observed that protein content affected FN; however in the current study, the CV of FN and protein content, as well as their direct values, were uncorrelated (r < 0.2). The first situation, Washington 2014, represented the case when grain is sampled from the truck's dump stream during unloading.…”
Section: Discussioncontrasting
confidence: 75%
“…The current study was designed to address this answer while following the best laboratory practices established in the previous study. Ross et al (2012) observed that protein content affected FN; however in the current study, the CV of FN and protein content, as well as their direct values, were uncorrelated (r < 0.2). The first situation, Washington 2014, represented the case when grain is sampled from the truck's dump stream during unloading.…”
Section: Discussioncontrasting
confidence: 75%
“…Furthermore, there are many other conditions that, in addition to rainfall, influence the occurrence of PHS (Mares & Mrva, ). An additional challenge with PHS has been the range of observed responses (Barnard & Smith, ; Clarke, Christensen, & DePauw, ; Gooding, Ellis, Shewry, & Schofield, ; Jiménez et al, ; Lunn, Kettlewell, Major, & Scott, ; Okuyama, Fonseca Junior, Caramori, & Kohli, ; Ross et al, ; Shorter, Munro, & Hodgkinson, ; Smith & Gooding, ; Trethowan, Rajaram, & Ellison, ). Contributing to the diversity of responses will be environments studied (i.e., climatic; field vs. glasshouse design; and with and without intervention), diverse genotypes, and different ways to measure PHS (i.e., from dormancy to germination tests and falling number).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the elevator's practice, the penalty is either imposed in full (harshest) or in a graduated (unit‐by‐unit) structure within the 25 unit range ( personal communication , Washington Grain Commission). Recent research of Ross and coworkers (2012) suggests that FN values near 300 or lower for U.S. Pacific Northwest–grown wheat may occur in low‐protein‐content wheat that is not sprout damaged, whereby the protein acts to modulate FN in a positive relationship. Thus, the penalty for wheat lots having FNs below 300 may be even more dubious.…”
mentioning
confidence: 99%